Adherence to antihypertensive medications and its determinants among adult hypertensive patients - Sindu Punna; Sudhakar Kodudula; Vineela Karthik N (Journal of Krishna Institute of Medical Sciences University, 2022)
Background: Hypertension is an important noncommunicable disease and is one of the major but modifiable risk factors of cardiovascular disease. There are multiple reasons for the poor Blood Pressure (BP) control rates of which, lack of adherence is an important factor. Aim and Objectives: To assess antihypertensive medication adherence in hypertensives. To identify factors associated with adherence. Material and Methods: Across-sectional observational study was conducted among 400 hypertensive patients. Morisky Medication Adherence Scale (MMAS-4) was administered on them for assessing adherence to medications. Results: Fifty two point five percent of study participants had high adherence to antihypertensive medications. Statistically significant association to adherence was found among patients below 60 years, educated, married, high socioeconomic status, without co-morbidities and recent onset hypertensives. Conclusion: High adherence was associated with better control of blood pressure. Treatment of hypertension should be holistic and treating clinician should check for adherence especially in uneducated, low socioeconomic status, single, alcoholics, smokers and patients with co-morbidities. Public awareness campaigns should be conducted on the importance of hypertension control.